PENGARUH STRUKTUR MODAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG PADA PERUSAHAAN GROSIR YANG TERDAFTARDI BURSA EFEK INDONESIA (2017-2019) - SILALAHI, EVELIN ROMA RIAULI; NASUTION, SUSI ELISABETH (Jurnal Riset Akuntansi & Keuangan, 2022)
The aim of this study is to demonstrate the effect of Capital Structure (Longterm Debt to Asset Ratio and Debt to Equity Ratio) on Corporate Income Tax Payable. In Wholesale Companies that are listed on the Indonesia Stock Exchange between 2017 and 2019. Purposive sampling was used to obtain the sample for this study, which included 16 companies. Multiple linear regression and hypothesis testing with t-test and f-test with a significance level of 5% were used for data analysis in SPSS 24. The coefficient of determination (R Square) is 0.241, according to the findings of SPSS research. The long-term debt-to-asset ratio and the debt-to-equity ratio both have an impact on the corporate income tax payable, which is 24.1%. Based on the results of multiple linear regression analysis, it can be concluded that the Longterm Debt to Asset Ratio has a significant negative effect on Corporate Income Tax Payable in wholesale companies listed on the Indonesia Stock Exchange in 2017-2019, while the Debt to Equity Ratio has an insignificant positive effect. The higher the Longterm Debt to Asset and Debt to Equity Ratios, the lower the profit and the higher the Corporate Income Tax Payable